Methane production from oleate : assessing the bioaugmentation potential of Syntrophomonas zehnderi - Cavaleiro, A. J. (2010)
The potential for improving long-chain fatty acids (LCFA) conversion to methane was evaluated by bioaugmenting a non-acclimated anaerobic granular sludge with Syntrophomonas zehnderi. Batch bioaugmentation assays were performed with and without the solid microcarrier sepiolite, using 1 mM oleate as sole carbon and energy source. When S. zehnderi was added to the anaerobic sludge methane production from oleate was faster. High methane yields, i.e. 89 ± 5% and 72 ± 1%, were observed in bioaugmented assays in the absence and presence of sepiolite, respectively. Sepiolite stimulated a faster methane production from oleate and prevented the accumulation of acetate. Acetoclastic activity was affected by oleate in the absence of sepiolite, where methane production rate was 26% lower than in assays with microcarrier.